Surgical Apgar Score in Predicting Post-operative Outcomes in Neurosurgical Patients – A Prospective Observational Study - Shakya, Bikram; KC, Bidur; Shrestha, Ujma; Adil, Mohamed Zaidan; Shrestha, Sushan; Singh, Ranjan Raj (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: The Surgical Apgar Score (SAS) predicts postoperative outcomes in various surgical fields, but its utility in neurosurgery remains underexplored. This study evaluated SAS’s effectiveness in predicting complications, mortality, and hospital stay in neurosurgical patients. Methods: A prospective observational study was conducted on neurosurgical patients who underwent neurological surgery. SAS was calculated based on intraoperative blood loss, lowest heart rate, and lowest mean arterial pressure. Patients were categorized into three SAS groups (0 - 4, 5 - 7, and 8 - 10). Postoperative complications, mortality rates within 30 days, hospital stay and ICU stay durations were analyzed. Results: Among 150 patients, 40 (26.7%) experienced significant postoperative complications, commonest being infections in 15 (10%), prolonged coma in 11 (7%), and reoperation in eight (5%). Mortality was observed in 10 patients (6.7%). The mean hospital stay was longer for patients with complications (15 days) compared to those without complications (Eight days), and ICU stays were also prolonged in patients with lower SAS. Patients with a low SAS (≤ 4) had a 40% complication rate, whereas those with a high SAS (≥ 8) had a 10% complication rate (P < 0.05). Lower SAS significantly predicted postoperative complications and mortality (P < 0.001). Conclusions: SAS effectively predicts postoperative outcomes in neurosurgical patients. Its integration into perioperative decision-making may enhance patient care.